Exploring the effect of quranic rhythm therapy for tinnitus sufferers - Othman, Nik Adilah Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2015)
To determine the status of tinnitus management provided by three different professionals in Otorhinolaryngology (ORL) Department ORL specialists, Audiologists and medical officers in local hospitals.